Estimasi Emisi Metana dari Fermentasi Enterik Terhadap Potensi Pemanasan Global pada Sektor Peternakan Sapi Perah di Kecamatan Lembang Kabupaten Bandung Barat - Ricky Fahrezy Ardiansyah; Didin Agustian Permadi (Fakultas Teknik, 2022)
Lembang District is one of the sub-districts in West Bandung Regency with the largest population of dairy cattle in West Java. an increase in the population of dairy cows will cause an increase in emissions that cause global warming. Methane is one of the greenhouse gas emissions produced from dairy cattle. Methane emissions from dairy cattle are produced when cattle burp and fart. In this study, the estimation of methane emissions from enteric fermentation uses the IPCC 2019 reference guidelines using tier 1 and tier 2. The results of calculations using tier 1 show that the highest methane emission from enteric fermentation is Sukajaya Village 8.0939 Gg CO2-eq/year and the highest is Sukajaya Village 8.0939 Gg CO2-eq/year. the lowest was Pangerwangi Village at 0.7057 Gg CO2-eq/year. Then the results of calculations using tier 2 based on local emission factors and development of emission factors show that the highest emission is Sukajaya Village at 4.8231 Gg CO2-eq/year using local emission factors, and 53.9276 Gg CO2-eq/year using development factors. emission. Meanwhile, the lowest methane emission is Pagerwangi Village at 0.0408 Gg CO2-eq/year using local emission factors. However, in the low calculation using the development of emission factors, the village that produces the lowest methane emissions is Wangunharja Village with emissions of 0.0495 Gg CO2-eq/year.